BIOSYNTHESIS, CHARACTERIZATION, AND ANTIBACTERIAL ACTIVITY OF SILVER NANOPARTICLES SYNTHESIZED FROM VEGETABLE PEELS (Journal of Medical & Health Sciences Review, 2025)
Silver nanoparticles (AgNPs) have garnered considerable attention for their potent antibacterial properties, offering promising applications in various fields, including medicine and industry. This study explored the eco-friendly biosynthesis of silver nanoparticles using potato peels (Solanum tuberosum) as a natural reducing and stabilizing agent and evaluated their antibacterial efficacy against pathogenic microorganisms. Potato peels serve as a cost-effective and sustainable source for AgNP synthesis. The reduction of silver ions will be monitored using UV-visible spectroscopy, while the morphology and structural characteristics of the nanoparticles will be analyzed through Fourier Transform Infrared Spectroscopy (FTIR) and X-ray Diffraction (XRD). The antibacterial activity of the synthesized AgNPs against Pseudomonas aeruginosa and Acinetobacter baumannii will be assessed using a good diffusion assay. The eco-friendly synthesis of silver nanoparticles with notable antibacterial properties highlights their potential applications in biomedical and industrial settings.